2010
DOI: 10.1159/000320755
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dysfunction in Patients with End-Stage Renal Disease

Abstract: Background: While chronic dialysis treatment has been suggested to increase pulmonary pressure values, right ventricular dysfunction (RVD) is a major cause of death in patients with end-stage renal disease. We investigated the impact of different dialysis treatments on right ventricular function. Methods: We examined 220 subjects grouped as follows: healthy controls (n = 100), peritoneal dialysis (PD; n = 26), hemodialysis (HD) with radial arteriovenous fistula (AVF; n = 62), and HD with brachial AVF (n = 32).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 45 publications
5
91
4
Order By: Relevance
“…Our study, similar to other ones, 5,8,27 showed an increased risk of PAH in patients on HD compared with patients on PD. Multivariate analyses in our study showed that this higher risk is independent of anemia, presence of AVF, level of creatinine, and degree of systolic and diastolic cardiac dysfunction.…”
Section: The Effects Of Dialysis Typesupporting
confidence: 92%
“…Our study, similar to other ones, 5,8,27 showed an increased risk of PAH in patients on HD compared with patients on PD. Multivariate analyses in our study showed that this higher risk is independent of anemia, presence of AVF, level of creatinine, and degree of systolic and diastolic cardiac dysfunction.…”
Section: The Effects Of Dialysis Typesupporting
confidence: 92%
“…The arteriovenous fistula causes a left-to-right shunt, leading to chronic volume overload and right ventricle function impairment [10,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Both these measures were significantly more compromised in the HD cohort. As long as CKD patients new to dialysis entered our RRT program, we were able to extend our observation in a larger study (Paneni et al, 2010), including 94 patients on HD, 62 dialyzed trough a radial AVF and 32 trough a brachial AVF, and 26 on PD, most of whom on nightly automated PD (APD), compared with 100 healthy controls matched for age, gender and BMI. Patients on RRT did not differ with regards to the prevalence of hypertension and diabetes and type of medications used.…”
Section: What We Have Donementioning
confidence: 70%